Education between alcoholic beverages. (Journal of Parents and Teachers, 2014)
The society is concerned about the excessive consumption of alcohol by its younger members. And not only is society concerned; So is WHO, FAD and teachers. The article offers data, ages and relevant information on alcohol consumption today, influenced by advertising, and presents an action plan to continue in the classroom.
Keywords: Alcohol; concern; data; information; excessive consumption; action plan.